The Effect of Phet Simulation Media on Critical Thinking Ability and Learning Outcomes of SMA Negeri Yokiwa - Ika Putra Viratama; Prihaten Maskhuliah (Edumaspul: Jurnal Pendidikan, 2022)
This study aims: (1) To determine the effect of learning using Phet simulation media on the critical thinking skills of Yokiwa State High School students. (2) Knowing the effect of learning using Phet simulation media on the learning outcomes of Yokiwa State High School students. (3) Knowing the effect of learning using Phet simulation media on critical thinking skills and learning outcomes of Yokiwa State High School students. Data collection using questionnaires and test instruments. The results showed that in learning using Phet's simulation media on critical thinking skills, there were differences that could be seen from the increase in critical students in the pattern of solving physics problems on Ohm's Law material and the series of Barriers. And there are differences in learning outcomes between before learning and after learning. It can be seen that learning outcomes after the implementation of Phet simulation are higher, this indicates that there is a significant effect on learning using Phet simulation media. From the results of linearity test data processing, it is known that the data has a linear pattern between learning using Phet (X) simulation media on critical thinking skills (Y1) and student learning outcomes (Y2) in class XII SMA Negeri Yokiwa. The deviation from linearty sign indicates this. > 0.005 then there is a significant linear relationship between the independent and dependent variables.